2019
DOI: 10.1111/jpi.12600
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on endothelial dysfunction in patients after acute coronary syndrome: The MEFACS randomized clinical trial

Abstract: Endothelial dysfunction (ED) precedes acute coronary syndrome. Oxidative stress results in ED but is reversible. Melatonin is aside from being a circadian hormone, also an antioxidant. The aim of this study was to investigate whether 25 mg melatonin administered for twelve weeks following acute coronary syndrome (ACS) could improve ED. In this placebo‐controlled randomized trial, ED was measured as reactive hyperemia index (RHI) at baseline, day 14, and day 84. The effect was assessed using a generalized estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…In another study, while melatonin regulated some markers of ED in vitro and its high dose of 10 mg sustained‐release tablets, three times daily, had clinical benefit in early onset preeclampsia, but it did not affect endothelial function or oxidative stress markers in studied patients 23 . Our results are also in contrast to a recent study, which demonstrated that 12 weeks of 25 mg oral melatonin did not improve endothelial function, measured by reactive hyperemia index, or its serum markers in patients after acute coronary syndrome 24 …”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In another study, while melatonin regulated some markers of ED in vitro and its high dose of 10 mg sustained‐release tablets, three times daily, had clinical benefit in early onset preeclampsia, but it did not affect endothelial function or oxidative stress markers in studied patients 23 . Our results are also in contrast to a recent study, which demonstrated that 12 weeks of 25 mg oral melatonin did not improve endothelial function, measured by reactive hyperemia index, or its serum markers in patients after acute coronary syndrome 24 …”
Section: Discussioncontrasting
confidence: 94%
“… 23 Our results are also in contrast to a recent study, which demonstrated that 12 weeks of 25 mg oral melatonin did not improve endothelial function, measured by reactive hyperemia index, or its serum markers in patients after acute coronary syndrome. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Acute inflammation response has been regarded as a signal to clear the damaged tissue whereas chronic inflammation reaction seems to be a process related to tissue repairing (Cao et al, 2019;Eiringhaus et al, 2019). In our study, we found that the levels of acute and chronic inflammation response were significantly elevated by oxidative stress and (Oliveira et al, 2019;Zahid et al, 2019).…”
Section: Discussionsupporting
confidence: 49%
“…Pretreatment with melatonin during five days before coronary artery bypass grafting surgery reduced myocardial injury, heart rate, oxidative stress, and inflammatory markers when compared to placebo [ 240 ]. On the other hand, 25 mg melatonin administered for twelve weeks following acute coronary syndrome may aggravate endothelial dysfunction [ 241 ]. Interestingly, the combination of 50 mg intravenously and 10 mg orally display cardioprotection in patients undergoing abdominal aortic aneurysm repair, with a risk reduction of 25% of cardiac morbidity, including postoperative atrial fibrillation [ 242 ].…”
Section: Melatonin As a Potential Antiarrhythmic Treatment In Aginmentioning
confidence: 99%